The Influence Of Work Environment And Work Motivation On Employee Performance At Bbppmpv Business And Tourism - Haikal, Sayid; Utama, Rony Edward (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study aims to analyze the influence of work environment and motivation on employee performance at BBPPMPV Business and Tourism. The research sample consisted of 65 employees taken through a random sampling method. Data were collected through a questionnaire covering variables of work environment, motivation, and employee performance. The analysis method used is multiple linear regression analysis with validity, reliability, classical assumption, and hypothesis testing. The results of the study indicate that the variables of work environment and work motivation have a positive and significant effect on employee performance. The work environment has an influence of 47.8%, while work motivation has an influence of 59.0%. The results of the determination coefficient test show that both variables together affect employee performance by 78.8%. Thus, it can be concluded that a conducive work environment and high motivation can improve employee performance at BBPPMPV Business and Tourism. This study provides implications that companies need to pay attention to both factors to improve employee productivity and performance.